Pathogenesis of renal failure in cirrhosis and fulminant hepatic failure. Issue 598 (August 1975) - Wilkinson, S. P.; Hurst, D.; Portmann, B.; Williams, Roger
Abstract : Acute renal failure in cirrhosis and fulminant hepatic failure represents a spectrum with 'functional renal failure' at one end and acute tubular necrosis at the other. In fulminant hepatic failure the development of renal failure is not necessarily a measure of the severity of liver damage. Functional renal failure is due to active renal vasoconstriction which may, at least in fulminant hepatic failure, be initiated by systemic endotoxaemia.